Factors affecting willingness to accept foreign halal foods by urban Malaysian Malays / Hasman Abdul Manan ... [et al.] - Abdul Manan, Hasman; Ariffin, Shahira; Ratul Maknu, Tengku Sharifeleani; Ibrahim, Irwan; Jaafar, Harlina Suzana (Universit Teknologi MARA Cawangan Selangor, 2019)
The significant shifts in urbanites’ lifestyles have been the catalyst behind the increased in the consumption of foreign foods and beverages in Malaysia; particularly those made in western nations. Notably, Malaysia’s total import for food had risen significantly from RM26.7 billion in 2009 to RM42.6 billion and RM 45.4 billion, in 2014 and 2015 respectively. These days, urban Malaysian Malays are being inundated with various foreign Halal food products in local markets however, these can also leave them in a rather risky circumstance as the likelihood that some of these foreign food products are not suitable (i.e. Haram) for their consumptions, is relatively high. Halal food issues (namely those foods originated from non-Muslim countries) have created lots of anxieties within the Malaysian Malays’ society. Hence, this study aims to examine factors affecting willingness to accept foreign Halal foods by urban Malaysian Malays. Convenience sampling technique was used to obtain responses from 450 urban Malaysian Malays in designated areas within the Greater Kuala Lumpur/Klang Valley region. The results demonstrated urban Malaysian Malays willingness to accept foreign Halal foods were significantly affected by trust but displayed no relationships with subjective knowledge and attitude. Also, the insignificant attitude willingness relationship signified the presence of the attitude-behavior gap. The study’s outcomes may perhaps offer new understandings on urban Malaysian Malay markets particularly for global brand owners and marketers